2019
DOI: 10.1104/pp.18.01331
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Cloning of Grape Circular RNAs Identified the Cold Resistance-Related Vv-circATS1

Abstract: Circular RNAs (circRNAs) are widely distributed and play essential roles in a series of developmental processes, although none have been identified or characterized in grapevines (Vitis vinifera). In this study, we characterized the function of grape circRNA and uncovered thousands of putative back-splicing sites by global transcriptome analysis. Our results indicated that several reported circRNA prediction algorithms should be used simultaneously to obtain comprehensive and reliable circRNA predictions in pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
108
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 117 publications
(194 reference statements)
5
108
0
1
Order By: Relevance
“…Plant circRNAs showed different expression patterns, and 27 rice exonic circRNAs were found to be differentially expressed under phosphate‐sufficient and ‐starvation conditions (Ye et al ). Overexpression of Vv‐circATS1, a circRNA derived from glycerol‐3‐P acyltransferase (ATS1), improved cold tolerance in Arabidopsis, while the linear RNA derived from the same sequence is not able to do the same (Gao et al ). Recently, transcriptome analyses of plant drought response and transgenic studies in Arabidopsis thaliana have revealed a relationship between circRNA expression and drought resistance, indicating that circRNAs play a key role in plant drought resistance responses and can also be used as effective biomarkers for genetic improvement of crop drought resistance (Zhang et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Plant circRNAs showed different expression patterns, and 27 rice exonic circRNAs were found to be differentially expressed under phosphate‐sufficient and ‐starvation conditions (Ye et al ). Overexpression of Vv‐circATS1, a circRNA derived from glycerol‐3‐P acyltransferase (ATS1), improved cold tolerance in Arabidopsis, while the linear RNA derived from the same sequence is not able to do the same (Gao et al ). Recently, transcriptome analyses of plant drought response and transgenic studies in Arabidopsis thaliana have revealed a relationship between circRNA expression and drought resistance, indicating that circRNAs play a key role in plant drought resistance responses and can also be used as effective biomarkers for genetic improvement of crop drought resistance (Zhang et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Plant circRNAs have been found to function during fiber development, flowering, and fruit coloration based on spatial-and/or tissue-specific expression patterns (Tan et al, 2017;Wang et al, 2017c;Tong et al, 2018). The expression of plant circRNAs also responds to abiotic and biotic stimuli, including pathogen invasion (Zuo et al, 2016;Wang et al, 2017c;Zhou et al, 2017;Ghorbani et al, 2018;Xiang et al, 2018;Gao et al, 2019). For example, the accumulation of a set of circR-NAs is altered in kiwifruit upon canker pathogen infection (Wang et al, 2017c).…”
mentioning
confidence: 99%
“…However, the roles of circRNAs in MeJA-mediated signaling pathways in A. thaliana have not been reported. Similar to other stresses in various plants, such as drought stress in maize and A. thaliana [20], dehydration stress in wheat [25], and cold stress in grapevine [28], MeJA treatment in A. thaliana altered the expression profiles of circRNAs. In this study, among the 8588 identified circRNAs, 385 circRNAs were identified as DEcircRNAs between MeJA-treated and untreated seedlings.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, with the development of high-throughput sequencing technology, increasing numbers of circRNAs have been detected in plants and animals. In plants, circRNAs are closely related to plant development and stress responses, including biotic and abiotic stresses [20,[22][23][24][25][26][27][28]30,53]. However, whether circRNAs participate in the pathways of plant responses to hormones is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation